IDENTIFYING EMPLOYEE REQUIREMENTS OF 5 STAR LOCAL HOTELS IN JAKARTA IN FACING ASEAN ECONOMIC COMMUNITY - Abadi, Fiter; Soeprapto, Vishnuvardhana; Adam, Mochammad Riyadh (Academic Research Centre Services, 2016)
This study is significant for the local five star hotels in Indonesia to identify the needs of human resource improvements especially to face the ASEAN Economic Community. In tourism industry, especially in Hotel Industry, the quality of HR is very crucial since employees face customers in daily life. This research is focused on five star local hotel and the samples are taken from five star local hotels in Jakarta with comparison of international five star hotel. To be more comprehensive, this research as well takes on tourism high school in Jakarta. As five stars hotels, customers are varying from their intention to stay and their nationalities. Therefore, employees are strongly needed to speak fluent English so that they can serve the customers well. However, based on the interview with local five star hotel, only limited employee can speak English and therefore it is needed to have English training as one of the priorities in every hotel. Secondly in it founded that tourism high school as the source of potential employee have done many training and focus on skills for its students and the allocation of time for English skill cannot be maximize since the curriculum of the school on government regulation.